„Zabić Indianina w dziecku”. O kulturowym ludobójstwie w Kanadzie i sprawiedliwości tranzycyjnej z Kate Korycki rozmawia Anna Zawadzka [“Kill the Indian in the Child.” On cultural genocide and transitional justice in Canada. Kate Korycki in an interview by Anna Zawadzka] - Anna Zawadzka (Studia Litteraria et Historica, 2016)
“Kill the Indian in the Child.” On cultural genocide and transitional justice in Canada. Kate Korycki in an interview by Anna Zawadzka